The implementation of reinforcement or students Positive motivation to improve learning activeness Inppknon the third class in sd negeri 49 limau Manis kulam - Gusni Gusni (Fakultas Sastra Universitas Ekasakti, 2017)
n order to learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to